“RESEARCH COLLABORATION AND LINKAGES WAS KEY AREA IN USM’S SELECTION AS OUR ERASMUS+ COUNTRY PARTNER INSTITUTION” – MIDDLESEX UNIVERSITY’S ERASMUS AND INTERNATIONAL EXCHANGE MANAGER - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
LONDON, February, 2016 Middlesex University’s ERASMUS and international Exchange Manager Dr. Nosheen Rachel Naseem revealed that USM was included as a country partner institution in its grant application for Erasmus+ International Credit Mobility funding on the basis of existing linkage between the two institutions in research collaboration.